Strengthening Digital Skills in Community Empowerment Through Online Marketing and Marketing Strategy Training - Siti Khotijah; Luluk Sarifah; Dina Raudlatul Jannah; Ulfatul Husna (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The gap in access to technology and community knowledge in Pragaan Daya village is a big challenge in efforts to strengthen digital skills through marketing training and online marketing strategies. The aim of this training is so that the people of Pragaan Daya Village can utilize digital technology in their daily economic activities. This activity was held on Saturday, August 20, 2022, at the Pragaan Daya Village hall and was attended by vocational and high school-level students and UMKM owners in Pragaan Daya Village. The methods used in this activity are seminars and training. The material in this training is an explanation of how an effective marketing strategy can make new products able to compete with products that have long been on the market, as well as practical steps and online marketing strategies. Strengthening digital skills provides benefits to the Pragaan Daya village community, including being able to more effectively promote their products and services, increase competitiveness, and expand market reach